2007
DOI: 10.1177/10717919070130030101
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effect of Leader-Member Exchange and Political Skill on Subjective Career Success

Abstract: Whereas previous research has examined the relationship between leader-member exchange (LMX) and objective measures of career success, it is likely that LMX is also an important predictor of subjective career success. Additionally, because of the political nature of an individual's career progression, it has been argued that one's personal style and resulting impressions are positively related to subjective career success. A sample of 295 retail workers was surveyed, and the results indicated that individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 61 publications
4
64
1
2
Order By: Relevance
“…They are knowledgeable on the manner and timing of their actions which enables them to acquire the result which is deemed best for them. This result supports previous research which have found subordinates with high LMX and high political skill are more confident to "speak up", but in instances when LMX is low, high political skill is required in order for them to have the confidence to speak up (Breland et al 2007). Overall, the results suggest the significance of UMT, in accounting an employee"s voluntary work behaviors such as speaking up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They are knowledgeable on the manner and timing of their actions which enables them to acquire the result which is deemed best for them. This result supports previous research which have found subordinates with high LMX and high political skill are more confident to "speak up", but in instances when LMX is low, high political skill is required in order for them to have the confidence to speak up (Breland et al 2007). Overall, the results suggest the significance of UMT, in accounting an employee"s voluntary work behaviors such as speaking up.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that subordinates with higher level of political skill are more likely to speak up even in instances of low LMX; and employees who have very strong political skills are more effectively engaged in "speaking-up" behavior. Thus subordinates who share high-quality LMX with the supervisor and possess high political skill are more confident to speak-up (Breland et al 2007). Particularly, employees who are politically-skilled are able to utilize opportunities or overcome threats in speaking-up carrying with them an increased control and understanding gained by political skill .…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In essence, political skill reflects individual differences in social ability to interact with authority. Previous research suggested that politically skilled people have higher supervisor-rated job performance (Hochwarter et al 2007;Liu et al 2007;Semadar et al 2006) and career success (Breland et al 2007;Semadar et al 2006).…”
Section: Group Power Distancementioning
confidence: 99%
“…Moreover by doing this, it enhances one's quantity and quality of life, and also helps in achieving career outcomes (such as career success) in the form of career prospect, career commitment as well as career satisfaction through his/her own work-related experiences (Judge et al, 1995;Seibert and Kraimer, 2001;Arthur et al, 2005;Heslin, 2003;Ng et al, 2005;Breland et al, 2007).…”
Section: Career Success and Its Variablesmentioning
confidence: 99%